2013
DOI: 10.2134/agronj2013.0238
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Harvest Lodging on Rough Rice Milling Yield and Market Price

Abstract: Lodging of a rice (Oryza sativa L.) plant just before harvest can significantly impact the quality of the harvested crop yield as well as the market returns received for sale of the crop. The purpose of this study was to quantify the level and significance of lodging on the milling yield and market price of rough rice. A 2‐yr study was conducted in the major rice‐growing regions of Arkansas, Louisiana, Mississippi, and Texas to evaluate the impact of early and late lodging before harvest. The study included tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 46 publications
0
20
0
2
Order By: Relevance
“…According to Salassi et al. (), rice quality and the actual productivity influence the market price of the rice and revenue of the area.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Salassi et al. (), rice quality and the actual productivity influence the market price of the rice and revenue of the area.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, sunn hemp was the cover crop species that most effectively benefited the cultivation of upland rice. According to Salassi et al (2013), rice quality and the actual productivity influence the market price of the rice and revenue of the area.…”
Section: Industrial Quality and Milled Rice Productivitymentioning
confidence: 99%
“…Lodging is a highly undesirable trait for rice as it slows harvesting operations, negatively impacts grain quality, and reduces grain yield . Salassi et al (2013) observed reductions in both whole grain rice milling yields (30.2 to 55.3 g kg -1 ) and total rice grain milling yields (7.8-10.9 g kg -1 ) when rice was manually lodged 5 to 7 d before fi eld drainage or 1 wk before harvest maturity. Modern, semi-dwarf rice varieties are generally considered to be more resistant to lodging than older tall varieties .…”
mentioning
confidence: 93%
“…This treatment significantly improves germination percentage, seedling emergence and seedling height and is especially important at sub-optimal temperatures (Dunand, 1992). As in small grains, lodging can also be a severe problem in intense rice production (Jennings and Sornchai, 1964;Moody, 1986;Nishiyama, 1986;Yoshinaga, 2005;Shibata and Takebayashi, 2007;Salassi et al, 2013). However, modern semi-dwarf cultivars produce relatively high yields, while being largely lodging-resistant.…”
Section: Ricementioning
confidence: 99%